Bi-columnar fixation of displaced distal humeral metaphyseal fractures in children: functional outcome assessment of 100 fractures - Gouse, Mohamad; Muthulingam, Manoharan; Rangarajan, Nandakumar (International Journal of Research in Orthopaedics, 2019)
Background: Supracondylar fractures of the humerus are one of the commonest fractures encountered around the elbow in children. The treatment of these fractures continues to pose challenges even in this age of advancing orthopedics. These fractures have the propensity to go for malunion with cosmetic deformity. This study was done to evaluate the functional results of surgical management of supracondylar fractures of the humerus in children using closed reduction and percutaneous bi-columnar pinning technique. Methods: 100 patients with Gartlands type II, III and IV supracondylar humerus fractures were operated with closed reduction and pinning using K-wires. Patients were followed up at six weeks, twelve weeks and six months and final evaluation were done using the Mayo elbow performance score (MEPS). Results: In our study, there were 70 males and 30 female patients with mean age of 6.5 years. 85 cases were had fall on outstretched hand as mode of injury and rest following motor vehicle accident. Gartland type II fractures accounted for 10 cases; type III fractures accounts 88 cases and type IV was only 2 cases. Excellent to good results were seen in 80 cases as per the MEPS at 6 months follow-up. Conclusions: From our study, we could conclude that closed reduction and bi- column percutaneous pinning offers a reliable fixation which permits early mobilization and good functional outcome in displaced fractures. Increasing the number of wire will allow early mobilization and prevent stiffness.